Applying 3D surface scanning technology to create photorealistic three-dimensional printed replicas of human anatomy - Lucy F Costello; Paul G McMenamin; Michelle R Quayle; John F Bertram; Justin W Adams (Future Science OA)
Aim: To describe advances in 3D data capture and printing that allow photorealistic replicas of human anatomical specimens for education and research, and discuss advantages of current generation printing for replica design and manufacture. Materials & methods: We combine surface scanning and computerized tomography datasets that maximize precise color and geometric capture with ultra violet (UV) curable resin printing to replicate human anatomical specimens. Results: We describe the process for color control, print design and translation of photorealistic 3D meshes into 3D prints in durable resins. Conclusion: Current technologies allow previously unachievable ability to capture and reproduce anatomical specimens, and provide a platform for a new generation of 3D printed teaching materials to be designed and used in anatomy education environments.